Academic Stress and Burnout Reduction Through Mandala-Coloring and Grit-Enhancing: School-Based Interventions for Adolescents - Xuening Fan; Anna Na Na Hui (Behavioral Sciences)
This quasi-experimental study evaluated the effectiveness of two school-based interventions aiming to reduce academic stress and alleviate burnout symptoms. Using cluster sampling, a total of 128 middle schoolers (Mage = 13.48, 42.2% female) from two classes in rural Henan Province, China, participated in this study. One class served as the control group (n = 61), while the other class was randomly assigned to two intervention groups: the mandala-coloring group (n = 31) and the grit-enhancing group (n = 32). ANCOVA and ANOVAs were conducted to detect any significant changes. The results showed that academic stress was significantly reduced in the mandala-coloring group (F = 5.741, p = 0.004, and η2p = 0.085), while no significant changes were observed in academic burnout. In the grit-enhancing group, a significant within-group increase in grit levels was found. These findings suggest that mandala coloring may serve as a time-efficient method for alleviating academic stress among adolescents. Implications for addressing academic stress and burnout in school settings are discussed.